Neuromodulation in psychiatry - Hamani, Clement; Holtzheimer, Paul E.; Lozano, A. M. (Andres M.), 1959-; Mayberg, Helen S. (Helen Susan), 1956- (John Wiley & Sons, Inc., 2016)
"Neuromodulation strategies, including both invasive and non-invasive approaches, are growing in popularity. Transcranial magnetic stimulation has been approved for the treatment of depression, and an increasing number of patients have access to this intervention. At the other end of the spectrum, deep brain stimulation is showing promise for patients with severe, treatment-resistant psychiatric illness. Other neuromodulation approaches are in various stages of clinical use and/or investigation. Importantly, many of these approaches are no longer limited to tertiary centers, but can be office-based for greater accessibility. This book provides a comprehensive and detailed guide to the use of neuromodulation strategies in psychiatry. It begins with a review of the history of this controversial field and the lessons learned, followed by a chapter on the ethics of modern usage of such techniques. Subsequent chapters are devoted to neuromodulation and surgical strategies used in psychiatry, including transcranial magnetic stimulation, transcranial direct current stimulation, vagus nerve stimulation, direct cortical stimulation, and deep brain stimulation. For each technique, a chapter describes the basic principles of each technique, using figures and schematics to illustrate details for people who do not have personal experience of using these techniques. Another chapter then focuses on the results of clinical research, trials and applications for that strategy. The book is the first comprehensive reference work to cover all neuromodulation strategies now used or with potential use in psychiatry. It allows psychiatrists to evaluate results obtained using such strategies and to make decisions regarding the best course of treatment for their patients"--Provided by publisher.